(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
Hothouse periods, such as the mid-Cretaceous and early Eocene, were times of global warming with high levels of greenhouse gases, elevated temperatures, and ice-free poles that provide a case study for understanding past climate dynamics. This study examines the paleo-Ultisols from the Bajo Barreal Formation (BBF; Cenomanian) and the Las Flores Formation (LFF; early Eocene) in central Patagonia (southern region of the Golfo San Jorge Basin). Due to their prolonged soil formation, these well-developed paleosols serve as valuable climate indicators. These paleosols were analyzed using a multi-proxy approach to understand their significance during those two periods in the Southern Hemisphere. The BBF Ultisols (mid-Cretaceous, 51° paleo-S) display kaolinite-rich Bt horizons, formed under intense chemical weathering conditions and leaching processes, linked to a temperate and humid climate. On the other side, the LFF Ultisols (early Eocene, 52° paleo-S) with kaolinite-dominated Bt and/or Btv horizons reflect their formation under higher chemical weathering and leaching processes, under a temperate-tropical and humid climate. For the times of formation of both BBF and LFF paleo-Ultisols, both localities were within the Warm Temperate climate zone. In contrast, this zone currently extends to approximately 40° N and S latitude. Present-day Patagonia is in the Arid climate zone, with much drier and cooler climate that contrasts with the warmer, wetter conditions of the Cenomanian and early Eocene localities analyzed. These findings highlight significant latitudinal displacement of climate zones during hothouse periods, emphasizing their importance in understanding past climate dynamics and providing insights into future climate change scenarios.